The in vivo and in vitro metabolism and the detectability in urine of 3', 4'‐methylenedioxy‐alpha‐pyrrolidinobutyrophenone (MDPBP), a new pyrrolidinophenone‐type designer drug, studied by GC‐MS and LC‐MSn. Issue 7 (7th October 2013) - Meyer, Markus R.; Mauer, Sandra; Meyer, Golo M. J.; Dinger, Julia; Klein, Birgit; Westphal, Folker; Maurer, Hans H.; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> 3', 4'‐Methylenedioxy‐alpha‐pyrrolidinobutyrophenone (MDPBP), a designer drug of the pyrrolidinophenone‐type, was first seized in Germany in 2009. It was also identified in 'legal high' samples investigated in the UK. Therefore, the aim of the presented work was to identify its in vivo and in vitro phase I and II metabolites using gas chromatography‐mass spectrometry (GC‐MS) and liquid chromatography‐ion trap mass spectrometry (LC‐MSn). Furthermore, detectability of MDPBP in rat and human urine using standard urine screening approaches (SUSA) by GC‐MS and LC‐MSn was studied. The metabolites were isolated either directly or after enzymatic cleavage of conjugates by solid‐phase extraction (C18, HCX). The metabolites were then analyzed and structures proposed after GC‐MS (phase I) and LC‐MSn (phase II). Based on these identified metabolites, the following main metabolic steps could be proposed: demethylenation followed by methylation of one hydroxy group, aromatic and side chain hydroxylation, oxidation of the pyrrolidine ring to the corresponding lactam as well as ring opening to the corresponding carboxylic acid. Furthermore, in rat urine after a typical user's dose as well as in human urine, mainly the metabolites could be detected using the authors' SUSA by GC‐MS and LC‐MSn. Thus, it should be possible to monitor an application of MDPBP assuming similar toxicokinetics in humans. Finally, CYP2C19 and CYP2D6 could be identified as the isoenzymes mainly responsible for demethylenation. Copyright © 2013 John Wiley & Sons, Ltd.